Association of admission LDL cholesterol with clinical profile and 3-months outcomes after ischaemic stroke - Marino Costa; Kateryna Antonenko; Charlotte Berger; Marieta Peycheva; Marina P. Krasteva; Arsany Hakim; Eike I. Piechowiak; Moritz C. Kielkopf; Thomas R. Meinel; Marcel Arnold; Hakan Sarikaya; Mirjam R. Heldner (European Journal of Medical Research, 2026)
Abstract Background and aim We investigated whether admission LDL-C levels are associated with clinical profile and outcomes after acute ischaemic stroke by comparing patients stratified into five LDL-C groups. Patients and methods We retrospectively analyzed consecutively included patients ≥18 years admitted to the Bernese Stroke Centre (02/2015–03/2023). Patients were stratified into five LDL-C groups: >3.0 mmol/L (n=493), 2.6–3.0 mmol/L (n=225), 1.8–2.6 mmol/L (n=490), 1.4–1.8 mmol/L (n=254) and